Historical dimension of the railway network, its economic and urban impact in san josé de cúcuta (2020)
The research aims to analyse the process of coverage of the railway network from England to San José de Cúcuta - Colombia, its impact as a transport system in the urban configuration.The research follows a qualitative approach from documentary analysis, which explores the historical particularities that make this process a significant event in the history of Colombia and the city of Cúcuta and quantitative by analysing mathematical models in productivity. It is concluded that the railway allowed the commercial exchange and development of the region, achieving its highest productivity in the thirties, and initiates a potential decline in the forties.